Nature, Economy and Society Understanding the Linkages - Ghosh, Nilanjan; Mukhopadhyay, Pranab; Shah, Amita; Panda, Manoj; SpringerLink (Online service) (New Delhi : Springer India(Imprint), 2016)
This book presents an enquiry into the interface between nature, economy and society, which is still in its early stages, notwithstanding the commendable progress and advances made in the field of environmental and natural resource economics within the ever-expanding boundaries of economics as a discipline. It further delineates the evolution of an inter-disciplinary framework for analyzing the status, the future goals, mechanisms and policy instruments that can help move towards a more ecologically sustainable, economically beneficial and socially just future. A pre-requisite for preparing a comprehensive and coherent framework involves unfolding the multiple layers of interconnectedness between the three systems nature, economy and society, each of which has its own internal consistencies as well as externalities. Against this backdrop, the book presents scholarly contributions that focus on four broadly defined building blocks, namely: i) accounting for ecosystems services for life and human well-being; ii) impacts of economic growth on ecosystems; iii) social norms, equity, and governance; and iv) alternative approaches to green and socio-economic systems. The analyses, presented by some of the most eminent national and international scholars, address the major environmental challenges that nations around the world face today and consider which specific policy directions at the international and national level are needed. In particular, the choices India and South Asia now face, as development and environment both need to be addressed adequately, touch on many of these challenges.
Chapter 1. Ecological Economics: At the interface of nature, economy, and society -- Chapter 2. Nature, Economy and Society: Of values, valuation and policy-making in an unequal world -- Chapter 3. Social metabolism and environmental conflicts in India -- Chapter 4. Current status of environmental and economic accounting: Review of some countries experiences and way forward for India -- Chapter 5. Strengthening forest resource valuation and accounting system: a case of forest resources of Kerala, India -- Chapter 6. Urbanisation and water supply: an analysis of unreliable water supply in Bangalore city, India -- Chapter 7. Energetics of irrigation under surplus rainfall conditions -- Chapter 8. Governing firms' corporate environmental response: success or failure? Evidence from a panel data based analysis on solid waste management in agri-food processing sector of Sri Lanka -- Chapter 9. 'Livestock for Development' in resource constrained environment: Would induction of external buffalo breeds help? -- Chapter 10. Soil fertility management in semi-arid regions: The socio-cultural, economic and livelihood dimensions of farmers' practices- a case of Andhra Pradesh -- Chapter 11. Issues on forest governance in contemporary Odisha -- Chapter 12. Multifunctional benefits of community based mangrove restoration in Gujarat: An analysis -- Chapter 13. Linkages between environment and globalization: A case study of developing countries -- Chapter 14. Can the poor resist capital? Conflicts over 'accumulation by contamination' at the ship-breaking yard of Alang (India): How struggles for environmental justice contribute to the environmental sustainability of the economy -- Chapter 15. Environmental cost of shrimp farming in the coastal paddy lands of South India -- Chapter 16. Designing PAT as a climate policy in India: Issues learnt from EU-ETS -- Chapter 17. Persistence of Jhum cultivation: Social capital and labour market -- Chapter 18. Ecological and socio-economic impacts of Prosopis juliflora invasion into the semi-arid ecosystems in selected villages of Ramnad district in Tamilnadu.
Keywords: Environmental economics; Ecology; Development economics